(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
A notice of the discovery of ’Celtic’ tobacco pipes found near Bonnington. The pipes were found alongside coinage from the time of James VI, which Dr Wilson argues can be used to date these pipes to James VI’s reign.